Dziecko w wieży Babel czyli przygotowanie do wielojęzyczności na etapie wczesnoszkolnym - Strzemeska, Regina (Neofilolog, 2010)
The current Polish tendencies to promote only English language in primary schools and various constraints in the „building of multilingualismfriendly environment” in early education call for an urgent action. To meet European appeals for multilingualism from an early age, two languages could be introduced in kindergartens and schools even in the present reality. This would require a new approch to teacher training, teacher co-operation, good administrative decisions, co-operation with parents, and integrated teaching. These statements will be illustrated by positive examples taken from the life of a kindergarten and a primary school in Toruń and Gdańsk, Poland.